The Autonomous Development Strategies of Micro and Small Entrepreneurs Through Coorporate Social Responsibility in Bogor District of West Java - Faizal Maad; Sumardjo Sumardjo; Amiruddin Saleh; Pudji Muljono (International Journal of Science and Engineering, 2014)
The objective  of this  reseach were to: (1) analyze the level of autonomous of mikro and small entreprise (SMEs) entrepreneurs are empowered through Coorporate Social Responsibility (CSR); (2) analyze the dominant factors that influence autonomous of MSEs entrepreneurs  are empowered through CSR;  and (3) formulate an appropriate  a strategy  in developing autonomy of MSEs entrepreneurs through CSR. The reseach  was conduct  in the village built two companies running CSR in Bogor district involved 212  (SMEs) entrepreneurs which determined from population (450 SMEs entrepreneurs) by Solvin formula with level of error 5 % and drawn by cluster random sampling. Data collection was conducted from July to November 2013, and consisted  the primary and secondary data. Data analysis was simulated by using structural equation model (SEM ). The results showed that the degree  of autonomous MSEs entrepreneurs is low, its core was 36.89 out of 100.00. There are three strategies that must be done to develop of  autonomous MSEs entrepreneurs through  CSR, such as; (a) an increase the empowerment sustainable of MSEs entrepereneurs (b) improve the quality of  the environment  supporting MSEs and (c) an increase in intensity of  empowerment for MSEs entrepreneurs.